UTILIZAÇÃO DA PROGESTERONA DE LONGA AÇÃO INJETÁVEL EM PROTOCOLO DE IATF EM VACAS BRANGUS - Araújo, Anna Paula Neumann de (2022)
The fixed-time artificial insemination (FTAI) is already widely disseminated and defined, with pregnancy rates ranging from 30 to 65 %. The P4 used in protocols can be administrated in several ways, even injectable. The use of injectable P4 gives out benefits regarding animal health, reduction in environmental waste and residue, in addition to greater convenience in intramuscular application. The objective of this study was to evaluate a labor rate in Brangus cows, between two and six years old, average weight of 350 kg and BCS between 2,5 and 3,5 subjected to FTAI protocol, distributed in two groups, one with the use of injectable P4 and another with the use of the P4 vaginal implant, the pregnancy diagnosis was performed by transrectal US, 45 days after the AI. According to the results, no statistical difference was observed in the pregnancy rate between the groups (p>0.05), where the CG obtained a 52,00% a (26/50) pregnancy rate, in comparison to the P4G with 37,50% a (21/56). Also, no statistical difference was observed regarding the expression of estrus where in the CG 30% a (15/50) required the administration of buserelina, compared to the P4G where 44,6% a (25/56) received the ovulation inductor at the time of AI. It was concluded, therefore, that the use of injectable progesterone as a substitute of the conventional intra-vaginal implant of P4, presents itself as a viable alternative.